Chirale titan- und zirkoniumkomplexe mit dem 1-(8-Chinolyl)-2,3-dimethylcyclopentadienyl-Liganden - Enders, Markus; Rudolph, Ralph; Pritzkow, Hans (Journal of organometallic chemistry, 1997)
Reaction of 8-lithioquinoline with 2,3-dimethylcyclopent-2-en-1-one leads to 1-(8-quinolyl)-2,3-dimethyl-cyclopentadiene (1) after hydrolysis and H2O elimination in acidic solution. With strong bases 1 is deprotonated to the intensively red coloured anion 2.2 was converted to the trimethylsilyl derivative 3, which could be characterized by crystal structure analysis, 3 reacts with group 4 transition metal chlorides to the chiral trichlorotitanium and trichlorozirconium complexes 4 and 5. 4 was examined by crystal structure analysis and shows the expected interaction between the quinolyl nitrogen atom and the metal centre.